Rectal Colonization and Nosocomial Transmission of Carbapenem-Resistant Acinetobacter baumannii in an Intensive Care Unit, Southwest Nigeria - Odih, Erkison Ewomazino; Irek, Emmanuel Oladayo; Obadare, Temitope O.; Oaikhena, Anderson O.; Afolayan, Ayorinde O.; Underwood, Anthony; Adenekan, Anthony T.; Ogunleye, Veronica O.; Argimon, Silvia; Dalsgaard, Anders; Aanensen, David M.; Okeke, Iruka N.; et al. (Frontiers in Medicine, 2022)
Background Acinetobacter baumannii are of major human health importance because they cause life-threatening nosocomial infections and often are highly resistant to antimicrobials. Specific multidrug-resistant A. baumannii lineages are implicated in hospital outbreaks globally. We retrospectively investigated a suspected outbreak of carbapenem-resistant A. baumannii (CRAB) colonizing patients in an intensive care unit (ICU) of a tertiary hospital in Southwest Nigeria where genomic surveillance of Acinetobacter has hitherto not been conducted. Methods A prospective observational study was conducted among all patients admitted to the ICU between August 2017 and June 2018. Acinetobacter species were isolated from rectal swabs and verified phenotypically with the Biomerieux Vitek 2 system. Whole genome sequencing (WGS) was performed on the Illumina platform to characterize isolates from a suspected outbreak during the study period. Phylogenetic analysis, multilocus sequence typing, and antimicrobial resistance gene prediction were carried out in silico. Results Acinetobacter isolates belonging to the A. baumannii complex were recovered from 20 (18.5%) ICU patients. Single nucleotide polymorphism (SNP) analysis and epidemiological information revealed a putative outbreak clone comprising seven CRAB strains belonging to the globally disseminated international clone (IC) 2. These isolates had ≤2 SNP differences, identical antimicrobial resistance and virulence genes, and were all ST1114/1841. Conclusion We report a carbapenem-resistant IC2 A. baumannii clone causing an outbreak in an ICU in Nigeria. The study findings underscore the need to strengthen the capacity to detect A. baumannii in human clinical samples in Nigeria and assess which interventions can effectively mitigate CRAB transmission in Nigerian hospital settings.